Demonstration of the protective effect of ghrelin in the livers of rats with cisplatin toxicity - Bademci, Refik; Erdoğan, Mümin Alper; Eroğlu, Ersan; Meral, Ayfer; Erdoğan, Arife; Atasoy, Özüm; Erbaş, Oytun (SAGE Publications Inc., 2021)
Despite the various and newly developed chemotherapeutic agents in recent years, cisplatin is still used very frequently as a chemotherapeutic agent, even though cisplatin has toxic effects on many organs. The aim of our study is to show whether ghrelin reduces the liver toxicity of cisplatin in the rat model. Twenty-eight male Sprague Dawley albino mature rats were chosen to be utilized in the study. Group 1 rats (n = 7) were taken as the control group, and no medication was given to them. Group 2 rats (n = 7) received 5 mg/kg/day cisplatin and 1 ml/kg/day of 0.9% NaCl, Group 3 rats (n = 7) received 5 mg/kg/day cisplatin and 10 ng/kg/day ghrelin, Group 4 rats (n = 7) received 5 mg/kg/day cisplatin and 20 ng/kg/day ghrelin for 3 days. Glutathione, malondialdehyde (MDA), superoxide dismutase (SOD), plasma alanine aminotransferase (ALT) levels, and liver biopsy results were measured in rats. It was determined that, especially in the high-dose group, the MDA, plasma ALT, and SOD levels increased less in the ghrelin group as compared to the cisplatin group, and the glutathione level decreased slightly with a low dose of ghrelin, while it increased with a higher dose. In histopathological examination, it was determined that the toxic effect of cisplatin on the liver was reduced with a low dose of ghrelin, and its histopathological appearance was similar to normal liver tissue when given a high dose of ghrelin. These findings show that ghrelin, especially in high doses, can be used to reduce the toxic effect of cisplatin.
Keywords: Hepatotoxicity; Cisplatin; Ghrelin; Antioxidant; Toxicity